Comprehensive Investigation on the Potential of Fly Ash from New Source as Construction Material - Antoni Antoni; Florentcia Hartono; Steven Tanuwijaya; Kevin Wijaya; Agie Vianthi; Djwantoro Hardjito (Institute of Research and Community Outreach - Petra Christian University, 2021)
Fly ash has been highly advocated to be re-utilized as a construction material. The most common utilization is to partially replace cement in a low-percentage scheme. However, there are several other schemes available to potentially use fly ash as binder in concrete that have not been widely exercised, especially those utilizing it in high to very high volume. In those schemes, high-volume fly ash (HVFA) concrete might use more than 50% fly ash to replace cement. To exploit its self-cementing properties, with or without the addition of other compounds, such as calcium hydroxide, fly ash might be used in very high percentage of cement replacement. In geopolymeric system, fly ash acts as the precursor of a stable binder, with the presence of highly alkaline solution. This paper demonstrates a model to investigate the potential of fly ash in several binder systems. The results show that fly ash from a good source can be utilized as an alternative binder in several different schemes.